KONTROL KEDALAMAN SEBAGAI PARAMETER SIFAT FISIK DAN KIMIA PERAIRAN PANTAI DI PULAU DUTUNGAN KECAMATAN MALLUSETASI KABUPATEN BARRU PROVINSI SULAWESI SELATAN - Sirajudin, Haerany; Putri, Naadya Suharto (Riset Sains dan Teknologi Kelautan, 2022)
Some of the determining parameters in explaining the physical and chemical properties of waters include height from sea level, intensity of sunlight received, season, weather, water depth, air circulation, and cloud cover. Each water area certainly has different coastal characteristics, including depth and underwater topographic conditions. The water depth parameter is the topic of this research because it can be measured directly in the field and related to the physical and chemical properties of seawater through linear regression statistical analysis. The results of depth measurements obtained in the waters of Dutungan Island ranged from 4-44 m, showing that the deepest depth level of 44 m was found at stations 9 and 11. Based on the level of sea depth, it is included in the littoral zone which is at a depth of less than 50 m, this makes living things that live in this zone very much because sunlight can still enter and penetrate into the sea, and cause coral reefs to photosynthesize. In this study, the independent variable is depth and the dependent variable is temperature, salinity, pH, dissolved oxygen (DO) and turbidity. In addition, measurement and retrieval of hydrodynamic and sediment data were also carried out, to further complement information on the characteristics of Dutungan Island. The coefficient of determination on the variable temperature to depth is 0.224; the variable salinity is 0.224.